Konversi Biji Alpukat Menjadi Bio-oil Dengan Metode Pyrolisis Menggunakan Katalis Zeolit Alam - Agustin, Dian; Sahan, Yusnimar; Bahri, Syaiful (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The trend of fossil fuel demand is always increase by time in the world. Yet, petroleum oil as a non-renewable has been declining each year. It is necessary to find a new alternative fuel that can be renewed, such as to applied biomasses as resources energy. One of several potential biomasses can be converted to energy or bio-oil is the seed of an avocado because it’s contain so high fat fatty acid (FFA). This seed has not been used maximacally yet, so in this research this seed is converted into bio-oil by using pyrolysis method and natural zeolite as a catalyst. The purpose of this research is to get the highest yield of bio-oil by applied variation of ratio sample : catalyst (50:0, 50:1, 50:2, 50:3 g/g), and temperature variation of pyrolysis process is 270, 300, 330 ºC. Based on results in this research, the highest of bio-oil is 79,08 % found under condition ratio sampel : catalyst 50 :2 and pyrolysis temperature is 330 ºC. The bio-oil is analyzed and it’s density 0.988 g/ml, viscosity 7,560 cSt, acid value 0,1002 mg NaOH/ g sample,  flash point 56 ºC and heating value 17,354 MJ/kg. Based on GC-MS analyzed bio-oil were contained (2,4,4-trimethyl-2-pentene), (3,4,4-trimethyl-2- pentene), (Diisobutylene), (2,4,4-trimethyl-3-pentene) and (2-methyl-trimer- propene) with peak area (7,84%), (7,82%), (5,69%), (3,82%) and (3,58%).  Keyword :  Avocado seed, Bio-oil, Natural Zeolite, Pyrolysis